Comparison of auditory steady-state response and click-evoked auditory brain response in infants with different types and degrees of hearing loss. - Xiaoli Wang; Yangyang Cheng; Jing Shi; Xiangyun Sheng; Dan Wu; Yali Zhao; Danhui Li; Dinghua He; Hua Wang (Acta Oto-Laryngologica (Supplement), 2020)
Background: Auditory steady-state response (ASSR) and click-evoked auditory brain response (c-ABR) have been used for hearing assessment for decades years, the correlation of the two methods and the effects of type and degree of hearing loss (HL) to the correlation in infants younger than 6 months of age are unclear. Objectives: To compare the correlation of ASSR and c-ABR and then to analyse the effects of type and degree of HL on the correlation in infants younger than 6 months of age. Material and methods: Retrospective study comparing ASSR thresholds at various frequencies with c-ABR thresholds. 182 ears from 96 infants were assessed and classified according to types and degrees of HL. Results: The correlation coefficients were: 0.823, 0.864, 0.891, 0.871, 0.908, 0.915 and 0.913 between ASSR thresholds at 0.5, 1, 2, 4, 2–4, 1–2–4, 0.5–1–2–4 kHz and c-ABR thresholds respectively. The correlation coefficients in the group of sensorineural HL (SHL) (r = 0.763–0.900) were higher than conductive HL (r = 0.309–0.619) across all frequencies. The coefficients of severe-profound SHL (r = 0.595–0.790) were higher than mild-moderate SHL (r = 0.434–0.687) across all frequencies. Conclusions and significance: ASSR was one valuable cross-check measure by providing frequency specific information in auditory assessment.